1985
DOI: 10.1093/carcin/6.4.579
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin H synthase oxidation of benzidine and o-dianisidine: reduction and conjugation of activated amines by thiols

Abstract: Prostaglandin H synthase oxidized the carcinogens benzidine and o-dianisidine to their respective quinonediimines. Analysis of the reaction media by u.v./visible spectroscopy and liquid chromatography with electrochemical and radiochemical detection revealed that these quinonediimines can be both conjugated and reduced by glutathione, cysteine and N-acetylcysteine. Analysis of the purified conjugate formed between synthetic benzidinediimine and glutathione by proton magnetic resonance spectroscopy demonstrated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
1

Year Published

1985
1985
2012
2012

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 0 publications
1
12
0
1
Order By: Relevance
“…Recently, a N-acetylcysteine conjugate has been isolated from a peroxidase-H202-benzidine-N-acetylcysteine reaction mixture and also identified as 3-(N-acetylcysteine-S-yl)-benzidine (106). An analogous GSH conjugate has also been isolated from a prostaglandin H synthase-arachnidonate-benzidine-GSH reaction mixture (107). The DNA adducts isolated from the dog bladder after the in vivo 14C-benzidine administration was 10% N-(deoxyguanosin-8-yl)[N'-acetylbenzidine but the rest was unidentified.…”
Section: N-oxidationmentioning
confidence: 99%
“…Recently, a N-acetylcysteine conjugate has been isolated from a peroxidase-H202-benzidine-N-acetylcysteine reaction mixture and also identified as 3-(N-acetylcysteine-S-yl)-benzidine (106). An analogous GSH conjugate has also been isolated from a prostaglandin H synthase-arachnidonate-benzidine-GSH reaction mixture (107). The DNA adducts isolated from the dog bladder after the in vivo 14C-benzidine administration was 10% N-(deoxyguanosin-8-yl)[N'-acetylbenzidine but the rest was unidentified.…”
Section: N-oxidationmentioning
confidence: 99%
“…The peroxygenation mechanism for metabolism of ABZ is dramatically different from the electron transfer mechanism observed for PHS metabolism of benzidine, the diamine analogue of ABZ (12)(13)(14)(41)(42)(43)(44). Both chemical and enzymatic experiments indicate the oxidation of benzidine to one-electron (cation radical) and two-electron (benzidinediimine) oxidized products.…”
Section: H]abz To [mentioning
confidence: 92%
“…Wise et al (30) and Josephy and Iwaniw (31) have reported the formation of benzidineglutathione or benzidine-N-acetylcysteine conjugates during the peroxidase-catalyzed oxidation of benzidine to free radical intermediates in the presence of glutathione or N-acetylcysteine, respectively. Wise et al (30) and Josephy and Iwaniw (31) have reported the formation of benzidineglutathione or benzidine-N-acetylcysteine conjugates during the peroxidase-catalyzed oxidation of benzidine to free radical intermediates in the presence of glutathione or N-acetylcysteine, respectively.…”
Section: Dlscusslonmentioning
confidence: 99%